Adventively established Leptopilina japonica: a new opportunity for augmentative biocontrol of Drosophila suzukii - Marco Valerio Rossi-Stacconi; Paul K. Abram; Gianfranco Anfora; Elizabeth Beers; Antonio Biondi; Nicolas Borowiec; Juli Carrillo; Jana Collatz; Asia Colmagro; Benjamin Crossman Johnson; Kent Daane; Giovanni Dal Zotto; et al. (Journal of Pest Science, 2025)
The invasive spotted-wing drosophila, Drosophila suzukii , has emerged as a significant global pest over the past decade, threatening fruit production worldwide. The parasitoid Leptopilina japonica , presumed native to East Asia, has established adventive populations in Europe and North America and is increasingly recognized for its ability to parasitize substantial proportions of D. suzukii larvae across diverse habitats. Here, we provide a broad review of the biology, establishment, distribution, and potential impacts of L. japonica . Using field data from international monitoring programs, we document the seasonal dynamics of plant–host–parasitoid associations and assess evidence for L. japonica ’s impact on D. suzukii and non-target organisms. Findings indicate that L. japonica has successfully established in several areas where D. suzukii is present in Europe and North America, showing promise as a biological control agent to support sustainable pest management. Current data suggest it provides some suppression of D. suzukii populations with minimal non-target effects. However, long-term studies are necessary to clarify its food web interactions and efficacy as a biological control agent. In areas where L. japonica has been established, we propose its use in augmentative biological control programs to enhance its impacts in specific agricultural settings. Case-specific evaluations of its ecological effects and role in integrated pest management, supported by continued monitoring, are essential. The case of L. japonica illustrates the need for clear, research-informed policies to guide the use of adventively established non-indigenous natural enemies in pest management.

E-nose based control charts for fish freshness evaluation - Susanna Buratti; Silvia Grassi; Paolo Giuseppe Ubaldi; Alberto Pianezzola; Simona Benedetti (Food Research International, 2025)

Use of ultrasound and NIRs as tools for monitoring ice formation in superchilled meat - Silvia Grassi; Antonio Jiménez; Jorge Ruiz; Alberto González-Mohino (Journal of Food Engineering, 2024)

High promiscuity among females of the invasive pest species Drosophila suzukii - Simone Puppato; Giulia Fiorenza; Davide Carraretto; Ludvik Marcus Gomulski; Giuliano Gasperi; Carlos Caceres; Alberto Grassi; Maria Vittoria Mancini; Antonio De Cristofaro; Claudio Ioriatti; Robin Guilhot; Anna Rodolfa Malacrida (Molecular Ecology, 2023)
Drosophila suzukii (Matsumura, 1931), the spotted‐wing drosophila, is a highly invasive fruit fly that spread from Southern Asia across most regions of Asia and, in the last 15 years, has invaded Europe and the Americas. It is an economically important pest of small fruits such as berries and stone fruits. Drosophila suzukii speciated by adapting to cooler, mountainous, and forest environments. In temperate regions, it evolved seasonal polyphenism traits which enhanced its survival during stressful winter population bottlenecks. Consequently, in these temperate regions, the populations undergo seasonal reproductive dynamics. Despite its economic importance, no data are available on the behavioural reproductive strategies of this fly. The presence of polyandry, for example, has not been determined despite the important role it might play in the reproductive dynamics of populations. We explored the presence of polyandry in an established population in Trentino, a region in northern Italy. In this area, D. suzukii overcomes the winter bottleneck and undergoes a seasonal reproductive fluctuation. We observed a high remating frequency in females during the late spring demographic explosion that led to the abundant summer population. The presence of a high degree of polyandry and shared paternity associated with the post‐winter population increase raises the question of the possible evolutionary adaptive role of this reproductive behaviour in D. suzukii .

First report on classical biological control releases of the larval parasitoid Ganaspis brasiliensis against Drosophila suzukii in northern Italy - Lorenzo Fellin; Alberto Grassi; Simone Puppato; Alberto Saddi; Gianfranco Anfora; Claudio Ioriatti; Marco Valerio Rossi-Stacconi (BioControl, 2023)
Current management strategy of the invasive fruit fly Drosophila suzukii (Matsumura) (Diptera: Drosophilidae) exploits different tools but relies mainly on chemical control. In the invaded areas, the local natural enemy community mostly consists of generalist pupal parasitoids unable to control the pest efficiently. Conversely, in the pest native area, there are more specialized sympatric larval parasitoids attacking D. suzukii . Following foreign explorations and quarantine risk assessments, the larval endoparasitoid Ganaspis brasiliensis (Ihering) (Hymenoptera: Figitidae) was selected as the best candidate for classical biological control programs. In 2021, the first ever propagative biocontrol program using a Japanese G1 lineage of G. brasiliensis started in Italy. Here we report the results of the first year of releases in the province of Trento (Northeast Italy), wherein G. brasiliensis was released in 12 locations. Pre- and post-release samplings on fresh and fallen fruits were performed around the release points to assess the recapture rate, the impact of the exotic parasitoid on D. suzukii and its potential interactions with local non-target species. After releases, G. brasiliensis was recovered at 50% of the locations. The exotic parasitoid only emerged from D. suzukii , mostly from fresh fruit still on the plant. Post-overwintering monitoring revealed the presence of a four G. brasiliensis individuals at two release locations.

Letter to the Editor on “Prediction of Knee Kinematics at Time of Noncontact Anterior Cruciate Ligament Injuries Based on Bone Bruises” - Alberto Grassi; Piero Agostinone; Stefano Di Paolo; Stefano Zaffagnini (Annals of Biomedical Engineering, 2021)

Estimation of metabolic syndrome heritability in three large populations including full pedigree and genomic information - Francesca Graziano; Ginevra Biino; Maria Teresa Bonati; Benjamin M. Neale; Ron Do; Maria Pina Concas; Simona Vaccargiu; Mario Pirastu; Oscar Terradura-Vagnarelli; Massimo Cirillo; Martino Laurenzi; Mario Mancini; et al. (Human Genetics, 2019)

Augmentative releases of Trichopria drosophilae for the suppression of early season Drosophila suzukii populations - Marco Valerio Rossi Stacconi; Alberto Grassi; Claudio Ioriatti; Gianfranco Anfora (BioControl, 2019)

Optimized timing of parasitoid release: a mathematical model for biological control of Drosophila suzukii - Ferdinand Pfab; Marco Valerio Rossi Stacconi; Gianfranco Anfora; Alberto Grassi; Vaughn Walton; Andrea Pugliese (Theoretical Ecology, 2018)

Large-scale spatial dynamics of Drosophila suzukii in Trentino, Italy - Gabriella Tait; Alberto Grassi; Ferdinand Pfab; Cristina M. Crava; Daniel T. Dalton; Roger Magarey; Lino Ometto; Silvia Vezzulli; M. Valerio Rossi-Stacconi; Angela Gottardello; Andrea Pugliese; Giuseppe Firrao; et al. (Journal of Pest Science, 2018)

Drosophila suzukii population response to environment and management strategies - Nik G. Wiman; Daniel T. Dalton; Gianfranco Anfora; Antonio Biondi; Joanna C. Chiu; Kent M. Daane; Beverly Gerdeman; Angela Gottardello; Kelly A. Hamby; Rufus Isaacs; Alberto Grassi; Claudio Ioriatti; et al. (Journal of Pest Science, 2016)

Multiple lines of evidence for reproductive winter diapause in the invasive pest Drosophila suzukii: useful clues for control strategies - Marco Valerio Rossi-Stacconi; Rupinder Kaur; Valerio Mazzoni; Lino Ometto; Alberto Grassi; Angela Gottardello; Omar Rota-Stabelli; Gianfranco Anfora (Journal of Pest Science, 2016)

Ecomorphology of oral papillae and denticles of Zapteryx brevirostris (Chondrichthyes, Rhinobatidae) - Bianca de Sousa Rangel; Adriano Polican Ciena; Natascha Wosnick; Alberto Ferreira de Amorim; José Roberto Kfoury Junior; Rose Eli Grassi Rici (Zoomorphology, 2016)

Connective tissue growth factor: a crucial cytokine-mediating cardiac fibrosis in ongoing enterovirus myocarditis - Christine Lang; Martina Sauter; Gudrun Szalay; Giorgia Racchi; Gabriele Grassi; Giuseppe Rainaldi; Alberto Mercatanti; Florian Lang; Reinhard Kandolf; Karin Klingel (Journal of Molecular Medicine, 2008)

IL1-? and TNF-? induce changes in the nuclear polyphosphoinositide signalling system in osteoblasts similar to that occurring in patients with rheumatoid arthritis: an immunochemical and immunocytochemical study - Nicoletta Zini; Gina Lisignoli; Liliana Solimando; Alberto Bavelloni; Francesco Grassi; Lia Guidotti; Carmela Trimarchi; Andrea Facchini; Nadir Mario Maraldi (Histochemistry and Cell Biology, 2003)

Spectroscopic properties and related functions of the stigma measured in living cells of Euglena gracilis - Pier Alberto Benedetti; Giovanni Bianchini; Alessandro Checcucci; Romano Ferrara; Sergio Grassi; Dyana Percival (Archives of Microbiology, 1976)